The Effect of Using Wordwall Game Application Media on Economics Subjects on Student Learning Outcomes at SMA Negeri 2 Sanga Desa - Lestari, Ayu; Rachmawati, Diana Widh; Toyib, Muhammad (Indonesian Scientific Publication, 2024)
In this study, the problems found in the field are that the teaching and learning process is not optimal because students experience a form of learning difficulties related to characteristic, personality and study habits or students who excel below their ability level (wordwaall game). By applying synectic learning media, it is expected to overcome or at least direct adjustments to the problems faced by students. This study aims to determine the learning interest of grade XI IPS 1 students in economic growth and development at SMA Negeri 2 Sanga Desa. The method used in this study is the experimental method. Based on the results of the study, the results of the student wordwall game test showed that the average student who experienced it was 85.66% in the experimental class. In the synectic model category, the average student activity is 46.66% and in the experimental class learning outcomes students have an average Student activeness is 46.66%. The overall increase that occurred in students after applying wordwall game media synectic learning in the experimental class had an average of 85.66% or in the creteria